Diaphragm hernia after debulking surgery in patients with ovarian cancer - Sarah Ehmann; Emeline M. Aviki; Yukio Sonoda; Thomas Boerner; Dib Sassine; David R. Jones; Bernard Park; Murray Cohen; Norman G. Rosenblum; Dennis S. Chi (Elsevier, 2021)
Over 80% of patients with epithelial ovarian cancer present with advanced disease, FIGO stage III or IV at the time of diagnosis. The majority require extensive upper abdominal surgery to obtain complete gross resection. This may include splenectomy, distal pancreatectomy, partial hepatectomy, cholecystectomy, and usually diaphragmatic peritonectomy or resection. Following surgery, diaphragmatic hernia-a very rare but serious complication-may occur.We describe four cases of left-sided diaphragmatic hernia resulting after debulking surgery, which included left diaphragm peritonectomy and splenectomy, in patients with advanced ovarian cancer. In association with the current shift towards more extensive debulking surgery for ovarian cancer, more patients may present with postoperative left-sided diaphragm hernia, making the prevention, diagnosis, and management of this complication important to practicing gynecologic oncologists. Intraoperatively the diaphragm should be checked thoroughly to rule out any defects, which should be closed. A diaphragmatic hernia may be easily misdiagnosed because the patient can present with various symptoms. While rare, these hernias require prompt identification, intervention and surgical correction to avoid serious complications.